Analisis Tantangan Dan Peluang Kebijakan Non Tunai Melalui Aplikasi Quick Response Code Indonesian Standard (QRIS) - Risma Nur Kholifah; Rini Puji Astuti; Moh Lukman; Nurholis Mudioretno; Fitratul Amaliyah (Jurnal Ekonomi dan Bisnis Digital, 2024)
Bank Indonesia also requires efficient, fast, secure and reliable payment system support. That is the target of its implementation, the task of organizing and maintaining a smooth payment system. In implementing such tasks, Bank Indonesia must play an active role in payment system development. This study aims to determine the challenges and opportunities of non-cash policy through the QRIS application. In this study, the author used the research method of literature study. The results of this study show that some of the challenges and opportunities faced in the cashless policy through QRIS application in Indonesia are unstable technology infrastructure and instability of technology infrastructure can hinder the adoption and use of QRIS, especially in rural areas.